Statistics for business and economics / James T. McClave, P. George Benson, Terry Sincich. - McClave, James T. (Prentice Hall international editions, 1998)
This edition of the comprehensive introductory text prepares today's business students to think critically about reported data and to use appropriate statistical methods to make good decisions